Carrier, Tracked 5-1/2-Ton (Nodwell RN 110D). Phase I. Subarctic Evaluation. - ARMY GENERAL EQUIPMENT TEST ACTIVITY FORT LEE VA (1962)
The The nodwell carriers RN 110D-1 and RN 110D-2 are highly mobile tracked cargo carriers, each capable of traversing difficult terrain with a payload of 11,000 pounds. Although these vehicles were designed primarily as cargo vehicles, they also have a limited towing capability. The steering system is air controlled, hydraulically actuated, with controlled differential, equipped with outer planetary reduction gears. The controlled differential an also be used for braking by activating the steering levers simultaneously. The vehicles have ur axles; each axle supports two 12-ply pneumatic tires. Each wheel has an independent crank arm wit torsion spring suspension, allowing considerable independent vertical movement. Each track consists of two parallel 15-inch wide belts of nylon-cotton reinforced rubber, connected by heat-treated spring steel grouser bars, that extend the width of the track. The tires ride in a concave pocket formed in the center of the grouser bars. Power is transferred from the differential to the track by rear-drive sprockets of steel overlaid with rubber or cast iron. (Author)